Applications of utility tunnels for natural gas pipelines - Apak, Mustafa Yurdabal; Ozen, Halit; Calis, Metehan; Golgeli, Baris; Ataoglu, Senol (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The scope of this article is to provide environmentally friendly, sustainable and safe infrastructure services for end-users with utility tunnels, including continuous flow systems, one of the transportation modes. Sustainable infrastructure systems are of great importance for urban highway planning and city construction site management. The implementation of utility tunnel systems in cities has emerged in recent years with the acceleration of urban transformation in Turkey. Initially, utility tunnel applications were limited and partially sheltered large campuses such as organized industrial zones, university campuses, and large sites. Implementations of utility tunnels are planned within urban transformation works, especially in metropolitan cities. However, it should not be ignored that there are essential points to be considered in these investment activities, which are carried out by various institutions at different times and planned to prevent damaging other infrastructures and the environment. It should not be forgotten that underground spaces filled by gas leaks are potential areas that cause explosions. This article aims to guide decision-makers and engineers to pay attention to the correct planning and implementation of utility tunnels in urban areas in Turkey. Application methods have been researched for the correct positioning of infrastructures and especially natural gas lines while applying utility tunnels. Additionally, examining the national and international applications and revealing the pros and cons of utility tunnels is also intended to help the correct choice of decision-makers and engineers. Infrastructure damages that cause gas leaks have been examined, and what needs to be done for the safer operation of natural gas lines has been discussed. The extent of the damage that occurred in the natural gas lines during or after constructing the infrastructures with the traditional open-cut trenching was searched. Instead of the traditional open-cut excavation method, the importance of utility tunnel applications for sustainable and safer urban life has been emphasized while natural gas lines are planned correctly through the use of utility tunnels in urban areas.
Keywords: Utility tunnel; Infrastructure; Natural gas pipeline; Damages; Gas leakage; Gas explosion accident; Turkey; URBAN UNDERGROUND SPACE; VENTILATION SYSTEM; DECISION-MAKING; VULNERABILITY; OPTIMIZATION; EXPLOSION; Construction & Building Technology; Engineering